Effect of attitudes and beliefs on exercise tolerance in chronic bronchitis. - Morgan, A D (1983)
In 50 patients with chronic bronchitis the relation was assessed between exercise tolerance and pulmonary function and psychological factors, including subjective perception of exertion, mood, general psychiatric disturbance, and the attitudes and beliefs held by patients concerning themselves, their illness, and its treatment. Ventilatory capacity was significantly correlated with but a poor predictor of exercise tolerance. Subjective perception of exertion was most closely correlated with exercise tolerance. The distance walked in a 12-minute exercise test was significantly correlated with measurements of mood and with several attitudes and beliefs. Attitudes and beliefs greatly outweighed measurements of mood and ventilatory capacity as components in a multiple regression predicting distance walked in 12 minutes. This method of psychological assessment emphasises the importance of attitudes and beliefs in respiratory disability and may have useful applications in rehabilitation in other chronic diseases.